Methods in medical ethics critical perspectives - Tomlinson, Thomas, 1945- (New York ; Oxford : Oxford University Press, 2012)
This book systematically reviews a variety of methods for addressing ethical problems in medicine, accounting for both their weaknesses and strengths. Illustrated throughout with specific cases or controversies, the book aims to develop an informed eclecticism that knows how to pick the right tool for the right job.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: Medical ethics